Cross-sectional survey of treatment practices for urethritis at pharmacies, private clinics and government health facilities in coastal Kenya: Many missed opportunities for HIV prevention - Mugo, P; Duncan, S; Mwaniki, S; Thiong'o, A; Gichuru, E; Okuku, H; Van Der Elst, E; Smith, A; Graham, S; Sanders, E (2013)
Background While bacterial sexually transmitted infections (STIs) are important cofactors for HIV transmission, STI control has received little attention in recent years. The aim of this study was to assess STI treatment and HIV testing referral practices among health providers in Kenya. Methods In 2011 we assessed quality of case management for male urethritis at pharmacies, private clinics and government health facilities in coastal Kenya using simulated visits at pharmacies and interviews at pharmacies and health facilities. Quality was assessed using Ministry of Health guidelines. Results Twenty (77%) of 26 pharmacies, 20 (91%) of 22 private clinics and all four government facilities in the study area took part. The median (IQR) number of adult urethritis cases per week was 5 (2-10) at pharmacies, 3 (1-3) at private clinics and 5 (2-17) at government facilities. During simulated visits, 10% of pharmacies prescribed recommended antibiotics at recommended dosages and durations and, during interviews, 28% of pharmacies and 27% of health facilities prescribed recommended antibiotics at recommended dosages and durations. Most regimens were quinolone-based. HIV testing was recommended during 10% of simulated visits, 20% of pharmacy interviews and 25% of health facility interviews. Conclusions In an area of high STI burden, most men with urethritis seek care at pharmacies and private clinics. Most providers do not comply with national guidelines and very few recommend HIV testing. In order to reduce the STI burden and mitigate HIV transmission, there is an urgent need for innovative dissemination of up-to-date guidelines and inclusion of all health providers in HIV/STI programmes.